Local exhaust ventilation : aerodynamic processes and calculations of dust emissions /: aerodynamic processes and calculations of dust emissions. (2015) - Logachev, Ivan Nikolaevich; Logachev, Konstantin Ivanovich, 1968-; Averkova, Olga
No abstract available